All Hail to Black Art. The Writings of Jacek Kryszkowski - Muzyczuk, Daniel ((Dif)fusions: Relations between Literature and Art in Poland after 1945, 2019)
The article disusses Jacek Kryszkowski as an artist of the late avantgarde. He became active mainly in the 1980s was part of the neodada movement Chip In Culture that was a reaction against both the official art and the neoavantgarde structural practices of the 1970s. Kryszkowski became notorious for his actions that were directed against the seriousness of the institution of art as well as the fetishistic practices. The article discusses the texts and publications of Jacek Kryszkowski as an expansion of his artwork after the final dematerialisation.